PREVALENCE AND DRUG SENSITIVITY PATTERN OF STAPHYLOCOCCUS AUREUS IN POST-OPERATIVE SURGICAL ORAL & MAXILLOFACIAL INFECTIONS: Life Science-Microbiology - BATABYAL, BISWAJIT; BISWAS, SHIBENDU; CHAKRABORTY, SUKANTA; DESAI, PRITI D.; DE SARKAR, NAVONIL (International Journal of Life Science and Pharma Research, 2012)
The problem of infection has been persistent in the surgical world even after the introduction of antibiotics. Pathogens that infect surgical site can be acquired from the hospital environment or other infected patients. A total of 66 pus samples from post-operative oral & maxillofacial surgical infections were received in the Department of Microbiology, Gurunanak Institute of Dental Science & Research, Panihati, Kolkata, over a period of one year. The isolates were identified using standard laboratory procedures. All the isolates were tested for susceptibility to various commonly used antibiotics and screened for oxacillin susceptibility according to CLSI guidelines. Out of 66 pus samples received, 34 (51.5%) were culture positive for Staph. aureus. Methicillin resistance was documented in 14 (41.2%) of the Staph. aureus isolates. Highest efficacy was observed with linezolid (97.0%).All MRSA isolates were 100% sensitive to linezolid. The hospital acquired surgical site infection is alarming. Hospital disinfection and treatment protocols should be practiced.